Thung in the Boon Phawet Tradition Roi Et Province: Patterns and Beliefs Leading to the Creation of Contemporary Dance Thung Phawet Mahachati Preaching - Phonsan, Nucharin (Journal of Fine and Applied Arts Khon Kaen University, 2023)
The creation of Thung Phawet Mahachati Preaching aimed 1) Study patterns and beliefs from Thung in the Boon Phawet traditional Roi Et Province and 2) Create contemporary dance performances Thung Phawet Mahachati Preaching. The creation instruments consisted of an observation form and an interview form. The study found that the pattern of Thung Phawet in Roi Et is unique characterized by the bamboo weaving type is the most common are horses, elephants, tiers, and castles and found identifying the name of the creator of the Thung offering and the name of the deceased that the relatives made merit consecrated to by means of weaving or embroidery into the bamboo weaving. There are 2 types of beliefs about offering Thung. 1) Making merit by offering Thung It is believed that it will be well auspicious for life. And 2) The giving of alms believed to help the souls of the deceased escape from hell or karmic and ascends to heaven with Thung and also found the belief of the eight directions of the sanctity in the event area believed that it is a symbol of victory for the devils will come to deal in the Boon Phawet. The merits of the offering are said to describe the fields swaying and flowing with the wind. It is consistent with the eight directions, namely Burapha, Southeast, Thaksin, Hordi, Pachim, Payap, Udon and Isan. It is a belief since ancients. The research used the presentation in the form of contemporary dance the creative process is 1) Concepts and inspiration for creation 2) Creative design of dance steps 3) Dance moves 4) Performers 5) Costume design 6) Performance equipment and 7) Music for the performance. The form a presentation of the show is divided in 4 periods 1) Present to the way of life weaving Thung and Phawet banners 2) Present to the pattern of Thung 3) Present to the show The sway of Thung 4) Present to the merits of Thung offering costume design is a conservative and creative style consider the show that can movement the body. The show’s props consist of weaving futons, paint brushes, Phawet banners, bamboo poles and Thung banners. Music for the performance show has been rewritten by using folk instruments together with international instruments There is a chorus in the melody of the Isan preaching by divided the song in a total of 4 parts, 7 verse Thung Phawet Mahachati Preaching show reflecting development of the process and performances concept creation of works from scholars in the field of dramatic arts. Analysis of data and create contemporary dance.